2018
DOI: 10.1186/s13045-018-0603-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FLT3 in acute myeloid leukemia using ligand-based chimeric antigen receptor-engineered T cells

Abstract: BackgroundChimeric antigen receptor-engineered T (CAR-T) cells have extraordinary effect in treating lymphoblastic leukemia. However, treatment of acute myeloid leukemia (AML) using CAR-T cells remains limited to date. Leukemogenesis always relates with the abnormalities of cytogenetics, and nearly one third of AML patients have activating mutations in Fms-like tyrosine kinase 3 (FLT3) which reminded poor prognosis. Considering the FLT3 expressed in AML patients’ blast cells, it may be a new candidate target f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 40 publications
3
102
1
Order By: Relevance
“…In a previous study parental antibody 4G8 on its own did not affect colony formation and was not cytotoxic toward CD34‐positive human bone marrow cells . Likewise, two prior studies with T cells carrying CARs based on FLT3‐specific scFv antibody or FLT3 ligand reported normal human hematopoiesis in NSG mice transplanted with HSCs after treatment with the FLT3‐specific CAR T cells, and undisturbed colony formation of cord blood derived HSCs in the presence of CAR T cells, respectively . In contrast, in another recent report, a marked reduction in colony formation and HSC viability was observed upon exposure of HSCs to FLT3‐targeted CAR T cells .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In a previous study parental antibody 4G8 on its own did not affect colony formation and was not cytotoxic toward CD34‐positive human bone marrow cells . Likewise, two prior studies with T cells carrying CARs based on FLT3‐specific scFv antibody or FLT3 ligand reported normal human hematopoiesis in NSG mice transplanted with HSCs after treatment with the FLT3‐specific CAR T cells, and undisturbed colony formation of cord blood derived HSCs in the presence of CAR T cells, respectively . In contrast, in another recent report, a marked reduction in colony formation and HSC viability was observed upon exposure of HSCs to FLT3‐targeted CAR T cells .…”
Section: Discussioncontrasting
confidence: 68%
“…28 Likewise, two prior studies with T cells carrying CARs based on FLT3-specific scFv antibody or FLT3 ligand reported normal human hematopoiesis in NSG mice transplanted with HSCs after treatment with the FLT3-specific CAR T cells, and undisturbed colony formation of cord blood derived HSCs in the presence of CAR T cells, respectively. 53,54 In contrast, in another recent report, a marked reduction in colony formation and HSC viability was observed upon exposure of HSCs to FLT3-targeted CAR T cells. 55 Here we did not observe CAR-mediated killing of mobilized human CD34-positive HSCs by NK-92/4G8.…”
Section: Discussionmentioning
confidence: 68%
“…We believe that this was the main reason why the clinical response of CAR-T-22 is inferior to that of CAR-T-19. Recently, a report on the substitution of scFV with FMS-like tyrosine kinase-3 ligand [30] provided a novel strategy for overcoming the problem of targeted motif loss caused by gene mutation. In addition to the regulation mechanisms, another reason for the fixed expression of CD19 is that it plays an important role in the survival and proliferation of B cell malignancies.…”
Section: Stabilitymentioning
confidence: 99%
“…Early clinical studies of CAR T cells for AML are ongoing, exploring several targets including CD123 (9, 10), CD33 (11), C-type lectin-like molecule 1 (CLL-1) (12,13), and Lewis-Y (14). Additional targets under preclinical investigation include CD135 (FLT-3 receptor) (15)(16)(17), Folate receptor β (18), CD44v6 (19), WT1 (20), B7-H3 (21-23), CD70 (24,25), and CD7 (26). While clinical experience thus far has shown feasibility and safety of CAR T cells for AML, efficacy has been limited in comparison to CD19-CAR T cell therapy for ALL (11,14).…”
Section: Introductionmentioning
confidence: 99%